2013
DOI: 10.1097/mao.0b013e3182a036c9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prognostic Role of pSTAT3 Expression in Temporal Bone Squamous Cell Carcinoma

Abstract: Despite our preliminary results, the role of pSTAT3 in temporal bone SCC warrants further investigation in larger series because there is increasing evidence in preclinical models to indicate that inhibiting STAT3 phosphorylation can be a useful addition to different anticancer strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Consequently, they express mesenchymal components like vimentin and gain a migratory phenotype, which is correlated with an extensive bone erosion and a worse prognosis . Last, the role of activated (phosphorylated) signal transducer and activator of transcription 3 in temporal bone squamous cell carcinoma warrants further investigation because it has been implicated in cellular proliferation, anti‐apoptosis, invasion, and angiogenesis in various types of cancer, including head and neck cancers …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they express mesenchymal components like vimentin and gain a migratory phenotype, which is correlated with an extensive bone erosion and a worse prognosis . Last, the role of activated (phosphorylated) signal transducer and activator of transcription 3 in temporal bone squamous cell carcinoma warrants further investigation because it has been implicated in cellular proliferation, anti‐apoptosis, invasion, and angiogenesis in various types of cancer, including head and neck cancers …”
Section: Discussionmentioning
confidence: 99%
“…pSTAT3 over-expression occurs in a variety of malignancies, suggesting that STAT3 may be not only prognostically important but also a potential target for therapy, and several strategies are being developed to target the STAT3 signaling pathway. Unfortunately, Marioni et al 31 found no significant correlations between phosphorylated STAT3 expression in tumor cells and DFS or DSS in TBSCC patients.…”
Section: Biomarkers and Temporal Bone Carcinoma Prognosismentioning
confidence: 98%
“…29 In 2013, Marioni et al 30 studied the role of the tumor suppressor protein MASPIN in TBSCC, finding subcellular cytoplasmic MASPIN expression significantly higher in patients who had experienced no recurrence of their carcinoma. In the same year, Marioni et al 31 investigated the prognostic role of phosphorylated (activated) signal transducer and activator of transcription 3 (STAT3) in TBSCC. pSTAT3 over-expression occurs in a variety of malignancies, suggesting that STAT3 may be not only prognostically important but also a potential target for therapy, and several strategies are being developed to target the STAT3 signaling pathway.…”
Section: Biomarkers and Temporal Bone Carcinoma Prognosismentioning
confidence: 99%
“…Sections were pretreated using heat-mediated antigen 16,17 The slides were ultimately slightly counterstained with hematoxylin. Sections were pretreated using heat-mediated antigen 16,17 The slides were ultimately slightly counterstained with hematoxylin.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Immunohistochemical staining was performed using the Bond Polymer Refine Detection kit (Leica Biosystems, Newcastle upon Tyne, UK) in the fully automated Bond-maX system (Leica Biosystems) on 4-lm-thick formalinfixed, paraffin-embedded sections cut from each tumor sample. Sections were pretreated using heat-mediated antigen 16,17 The slides were ultimately slightly counterstained with hematoxylin. Appropriate positive and negative controls were used.…”
Section: Immunohistochemistrymentioning
confidence: 99%